The coordinates of Inclusive Architecture: between the concept of disability and sustainability (REVISTA NODO, 2021)
This work of reflection focuses its analysis on the paradigmatic relationship that inclusive architecture has with the conceptual and theoretical evolution of two aspects that underlie it: disability and sustainability.Disability, the initial engine of inclusive architecture, presents three models of conceptual paradigms (Palacios, 2008): the presidential model, the medical or rehabilitative model, and the social model of functional diversity (Guzman Castillo et al., 2010), which show a transition whose impli cations are clear in architectural interventions towards inclusion.For its part, sustainability also presents three positions that constitute an evolutionary approach to the concept itself, and, therefore, the way in which society has dealt with this problem. According to Madge (1997), the paradigm shifts of sustainability can be represented in three stages: green design, eco-design and sustainable design, which clearly mark the depth and level of commitment of society to this discourse.As a strategy for this analytical reflection, the coordinates are used as a location scheme, where the limited progress of architecture in terms of inclusion is clearly appreciated.
Keywords: Architecture; Disability; Inclusion; Sustainability